Knowledge Dissemination Based on Terminological Ontologies: Using eye Tracking to Further user Interface Design - Louise Pram Nielsen (Copenhagen Business School (CBS), 2015)
The primary focus of this PhD dissertation is an eye-tracking experiment examining target-user performance on so-called dual-entry modes representing Danish taxation terminology, to determine whether terminological ontologies should be included in the user interface. The conventional concept-oriented articles of term banks, which describe the meaning of a term by means of text, are combined with concept-oriented diagrams, which represent the meaning of a term by means of a terminological ontology displaying the underlying concepts, relations and characteristics. The latter provides the target users with overview and allows for the inference of consistent definitions, which in principle should benefit the target user.
hdl:10398/9168
Keywords: 650